КОМПЛЕКСНЕ ДІАГНОСТУВАННЯ РОЗВИТКУ ОСОБИСТОСТІ ЯК ОСНОВА ІНТЕГРОВАНОГО МЕДИКО-ПСИХОЛОГО-ПЕДАГОГІЧНОГО ПІДХОДУ У СТВОРЕННІ ОСВІТНЬОГО СЕРЕДОВИЩА (Педагогіка вищої та середньої школи, 2009)
The complex diagnosticating of personality's development in a contest of computer intergrated medical, pryellliogical and pedagogical approach in a creation of the educational environment.The experience of conducting of the monitoring researches of child's personality develoment in condition of modern educational establishment has been experience investigated in this article. The author proves that special attention to the personal and developing potensial of the educational environment has been provided thanks diagnosticating. The guestion of Introduction of pupils individuatized education and training har been silved effectively.